MOLECULAR CHARACTERIZATION OF THE σC-ENCODING GENE FROM NOVEL DUCK REOVIRUS - T. Yun; H. P. Chen; J. G. Hua; B. Yu; L. Chen; Z. Ni; W. C. Ye; C. Zhang (Journal of Animal and Plant Sciences, 2015)
We cloned and sequenced the σC-encoding gene of a novel duck reovirus (N-DRV) isolate ZJ00M. The σC gene is 966 bp long and is encoded by the third ORF of the S1 segment, a small protein of 321 amino acid residues (approximately 34.1 kDa). Expressed σC fusion protein in E. coli showed good antigenicity and immunogenicity in a western blotting assay and indirect immunofluorescence assays (IFA). The comparative sequence analyses indicated that N-DRV σC shared high identity levels with ARV species (classical MDRV and ARV) and a lower degree of identity with other orthoreovirus counterparts, but the sequence identities were no more than 45 %. As observed in classical MDRV and ARV σC protein sequences, some sequence motifs, conserved sequence motifs and/or functional domains were identified in the sequence of N-DRV σC. The phylogenetic analysis of σC/σ1 sequence revealed that N-DRV was different fromother orthoreovirus species groups but remained classified into the avian orthoreoviruses along with other ARVs, suggesting that N-DRV and classical MDRVs constitute a separate geno group relative to ARV. These results are important for future studies examining the structure, function and immunogenicity of N-DRV σC.
Keywords: Novel duck reovirus; σC-encoding gene; Expression; Phylogenetic analysis; Genotype